Study on Management of Blood Transfusion Therapy in Patients with Hereditary Spherocytosis - Shiyue Ma; Lingjian Tang; Chaoli Wu; Hui Tang; Xue Pu; Jinhong Niu (Applied Bionics and Biomechanics)
Hereditary spherocytosis (HS) is a chronic hemolytic disorder caused by inherited defects in the red blood cell membrane. This study discusses the treatment strategy for the decline in hemoglobin level in three HS probands with moderately severe or severe hemolysis and summarizes the appropriate laboratory tests that help improve clinical management of blood transfusion in HS patients. Three probands who were diagnosed with HS in our hospital and their family members were included in this study. Clinical data of the three families were reviewed to summarize their hematopoietic characteristics. DNA from all family members of the 3 HS probands was amplified by polymerase chain reaction (PCR) and sequenced by the Sanger method to assess genetic relation for HS. Based on the sequencing results, the type of mutated membrane protein in each proband was analyzed using the eosin-5′-maleimide (EMA) binding test and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The hemoglobin level was reduced in all 3 probands after different levels of infection. The fluorescence of EMA-labeled red blood cell (RBC) was decreased. DNA sequencing showed that His54Pro, Leu1858Val, and 6531-12C>T compound heterozygous mutations were present in the SPTA1 gene of patient I-1, Arg344Gln and c.609+86G>A heterozygous mutations were present in the SLC4A1 gene of patient II-1, and Leu2032Pro homozygous mutation was present in the SPTB gene of patient III-1. SDS-PAGE results demonstrated that the concentration of band 3 was reduced in II-1, whereas the levels of the corresponding mutant proteins in the other probands were unchanged. The family members of the respective patients presented mutations in major genes causing HS. The Leu2032Pro mutation identified in patient III-1 is a new missense mutation of the SPTB gene in the Chinese population that has never been reported in literature previously. The presence or absence of acute or chronic infections is a critical deciding factor for the treatment and clinical management of HS patient via blood transfusion. For patients with infections, hemoglobin concentration can be restored once the infection is controlled, thus obviating the need for proper infection control before blood transfusion.